HIF3α: the little we know. (14th November 2015) - Ravenna, Linda; Salvatori, Luisa; Russo, Matteo A.
Abstract : Hypoxia‐inducible factors (HIFs) are key regulators of the transcriptional response to hypoxic stress. Three inducible isoforms of HIF are present in mammals. HIF1α and HIF2α are the best characterized and structurally similar isoforms, while HIF3α is the most distantly related and is less studied. The HIF3α gene undergoes complex regulation and produces a large number of long and short mRNA splice variants, which are translated into different polypeptides. These molecules primarily act as negative regulators of HIF1α and HIF2α activity and transcriptional activators of target genes, according to the variant and the biological context. The present review provides an overview of the available, fragmented and sometimes contradictory information concerning the structure, expression and distinct roles of the HIF3α variants, in both hypoxic adaptation and in hypoxia‐unrelated activities. The pathological consequences of HIF3α deregulation are also illustrated. Abstract : HIF1α, HIF2α and HIF3α are regulators of the transcriptional response to hypoxia. The HIF3α gene produces several polypeptides which act as negative regulators of HIF1α and HIF2α activities and transcriptional activators of target genes. This review provides an overview of the structures, expression and distinct roles of the HIF3α variants and illustrates the pathological consequences of HIF3α deregulation.